2019
DOI: 10.1101/2019.12.20.885392
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSI2/VAL1 and HSL1/VAL2 function redundantly to regulate seed dormancy by controllingDOG1expression in Arabidopsis

Abstract: 27 28 DELAY OF GERMINATION1 (DOG1) represents a major quantitative locus for the genetic 29 regulation of seed dormancy in Arabidopsis. Accumulation of DOG1 in seeds leads to deep 30 dormancy and delayed germination. Here, we report that the conserved B3 DNA binding 31 domains of the transcriptional repressors HIGH-LEVEL EXPRESSION OF SUGAR 32 INDICIBLE GENE2/ VIVIPAROUS-1/ABSCISIC ACID INSENSITIVE 3-LIKE1 33 (HSI2/VAL1) and HSI2-LIKE1/ VIVIPAROUS-1/ABSCISIC ACID INSENSITIVE 3-LIKE2 34(HSL1/VAL2), which play c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 66 publications
0
6
1
Order By: Relevance
“…These studies suggested that the transcriptional repressors HSL1 and its homologue HSI2 could cooperate with different HDACs to participate in the regulation of gene expression. Interestingly, a recent study showed that HSI2 and HSL1 function redundantly to regulate seed dormancy by controlling DOG1 expression in Arabidopsis (Allen et al 2019). In the present work, although no interaction was found between SUVH4 and HDA19, it cannot rule out that SUVH4 might interact with another HDAC to regulate gene expression.…”
Section: Both Hda19 and Suvh5 Interact Physicallycontrasting
confidence: 80%
“…These studies suggested that the transcriptional repressors HSL1 and its homologue HSI2 could cooperate with different HDACs to participate in the regulation of gene expression. Interestingly, a recent study showed that HSI2 and HSL1 function redundantly to regulate seed dormancy by controlling DOG1 expression in Arabidopsis (Allen et al 2019). In the present work, although no interaction was found between SUVH4 and HDA19, it cannot rule out that SUVH4 might interact with another HDAC to regulate gene expression.…”
Section: Both Hda19 and Suvh5 Interact Physicallycontrasting
confidence: 80%
“…VAL1 has previously been found to physically interact with VAL2, multiple PRC1 and PRC2 components, and the transcriptional repressor SAP18 (Chen et al, 2018(Chen et al, , 2020Chhun et al, 2016;Jing et al, 2019;Qüesta et al, 2016;Xie et al, 2018;Yang et al, 2013a;Yuan et al, 2016). However, these studies do not provide information about VAL1's in planta protein interactions over time.…”
Section: The Effects Of Val1 On Developmental Timing May Be Partly Explained By Its Expression Patternmentioning
confidence: 99%
“…These results demonstrate that all five RY-sites are important for the expression of MIR156C, and that they function additively. Individual RY-sites have also been shown to interact additively to repress the VAL1-PRC2 targets FLC and DOG1 (Chen et al, 2020;Yuan et al, 2016).…”
Section: Val1 Regulates Vegetative Phase Change Via Mir156-dependent and Mir156independent Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations